Suplementación de ganado de leche con núcleos energético protéico. - Mateus Echeverría, Henry; Latorre Ramírez, Sergio J. (Corporación Colombiana de Investigación Agropecuaria - CORPOICA, 2018)
Ganado de leche-Ganadería leche